WRITTEN REQUESTS IN KENYAN ENGLISH: AN ILLUSTRATION OF L1 CULTURE ADAPTATION IN L2 ACQUISITION (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper seeks to illustrate the observation from studies on secondlanguage acquisition and use that culture-specific aspects of a given languagecan be adapted to the norms of the culture of the linguistic community thatwidely uses it as a second language. Specifically, the paper looks at howwritten requests are made in Kenyan English with reference to how they arein British English, its direct ancestor. It bases its discussion and conclusion ontwo types of data: a) judgment data in the form of preference choices interms of which request formulas are most likely to be used by a sample of ahundred and eleven respondents; b) production data in the form of nonelicited requests actually made to the author by his students. In both cases,the subjects were University of Nairobi students. The frequency counts ofwhich requests would most likely be used and of those which were actuallyused show the request structures used in Kenyan English to be shorter andmore limited in number than those in British English.